Gereja Sebagai Communion yang Bertanggungjawab: Sebuah Model Bergereja bagi Gereja Masehi Injili di Timor dalam Menuntaskan Persoalan Human Trafficking di Nusa Tenggara Timur - Jear Nenohai (PAX HUMANA, 2017)
This article is a literature review to offer an ecclesiology model for GMIT in the face of human trafficking issues in East Nusa Tenggara. The author designed the ecclesiology model of responsibility by collaborating on the idea of the ecclesiology of communion Zizioulas and the review of the parable of the "Good Samaritan" in the gospel of Luke 10: 25-37 through the Ethical paradigm of Emanuel Levinas. The Church as a trititarian fellowship is responsible for migrant workers from East Nusa Tenggara such as Samaria who helps the injured person whom he encounters amid the journey. The ecclesiology of responsibility then becomes the theological foundation for GMIT in realizing God's love for those vulnerable to being victims of human trafficking.Keywords: Human Trafficking, GMIT, Ecclesia, Communion, Responsibility, and The Good Samaritan.